2013
DOI: 10.1002/dys.1448
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Syntactic Awareness to Reading in Chinese‐speaking Adolescent Readers with and without Dyslexia

Abstract: This study investigated the relative contribution of syntactic awareness to Chinese reading among Chinese-speaking adolescent readers with and without dyslexia. A total of 78 junior high school students in Hong Kong, 26 dyslexic adolescent readers, 26 average adolescent readers of the same age (chronological age control group) and 26 younger readers matched with the same reading level (reading-level group) participated and were administered measures of IQ, syntactic awareness, morphological awareness, vocabula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 70 publications
(82 reference statements)
3
12
0
1
Order By: Relevance
“…Chinese vocabulary knowledge. Adapted from Chung, Ho, Chan, Tsang, and Lee (2013), 25 words were included in the vocabulary definitions knowledge measure. Students were asked to explain or define the given target words and then use the target words to construct sentences to illustrate that meaning.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Chinese vocabulary knowledge. Adapted from Chung, Ho, Chan, Tsang, and Lee (2013), 25 words were included in the vocabulary definitions knowledge measure. Students were asked to explain or define the given target words and then use the target words to construct sentences to illustrate that meaning.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Studies in alphabetic scripts have reported a functionally important phonological processing deficit in many dyslexics (Ramus, ; Ramus & Ahissar, ; Ramus, Marshall, Rosen, & van der Lely, ; Hoeft et al ., ; Shaywitz et al ., ; Boets et al ., ). In studies using Chinese characters, phonological problems were also found (Ho, Law, & Ng, ; Cheung et al ., ; Liu, Shu, & Yang, ), but these were not considered core deficits; rather, impairments in orthographic processing and morpheme awareness were thought to be more important (Ho, Chan, Tsang, & Lee, ; Ho, Chan, Lee, Tsang, & Luan, ; Chung, Ho, Chan, Tsang, & Lee, , ; Shu, McBride‐Chang, Wu, & Liu, ; Shu, Peng, & McBride‐Chang, ; Xiao & Ho, ).…”
Section: Introductionmentioning
confidence: 99%
“…Os conhecimentos morfossintáticos são também apontados na literatura como um bom preditor do desempenho na leitura, tendo especial relevância nas competências de nível superior, como a compreensão leitora, mas também nas competências básicas de leitura e escrita (Chung, Ho, Chan, Tsang, & Lee, 2013;Foorman, Petscher, & Bishop, 2012;Kruk & Bergman, 2013;McCutchen, Green, & Abbott 2008;Roman, Kirby, Parrila, Wade-Woolley, & Deacon, 2009;Scull, 2013;Tong, Tong, Shu, Chan, & McBride-Chang, 2014).…”
Section: Introductionunclassified